An inner membrane complex protein IMC1g in Plasmodium berghei is involved in asexual stage schizogony and parasite transmission - Yinjie Liu; Shitong Cheng; Gang He; Dawei He; Duo Wang; Sicong Wang; Lumeng Chen; Liying Zhu; Yonghui Feng; Liwang Cui; Yaming Cao; Xiaotong Zhu (mBio)
ABSTRACT The inner membrane complex (IMC), a double-membrane organelle underneath the plasma membrane in apicomplexan parasites, plays a significant role in motility and invasion and confers shape to the cell. We characterized the function of PbIMC1g, a component of the IMC1 family member in Plasmodium berghei. PbIMC1g is recruited to the IMC in late schizonts, activated gametocytes, and ookinetes. Pairwise yeast two-hybrid assays demonstrate that PbIMC1g interacts with IMC1c, a component of the PHIL1 complex, and the core sub-repeat motif “EKI(V)V(I)EVP” in PbIMC1g is essential for this interaction. Localization of PbIMC1g to the IMC was dependent on its IMCp domain, while its C-terminus and palmitoylation sites were required for the full efficiency of proper IMC targeting. PbIMC1g is required for asexual stage development, and its conditional knockdown resulted in a defect in schizogony. Additionally, PbIMC1g was also important for male gametogenesis and ookinete development. As an IMC component that assists in anchoring the glideosome to the subpellicular network, PbIMC1g was also involved in ookinete motility and mosquito midgut invasion. IMC1g from the human parasite Plasmodium vivax could functionally replace PbIMC1g in P. berghei, confirming the evolutionary conservation of IMC1g proteins in Plasmodium spp. Together, this work reveals an essential role of IMC1g in the parasite life cycle and suggests that IMC1 family members likely contribute to parasite gliding and invasion.IMPORTANCEThe malaria parasite’s inner membrane complex is critical to maintain its structural integrity and motility. Here, we identified the function of the IMC1g protein, a member of the IMC1 family, in invasive and proliferative stages of P. berghei. We found that the IMCp domain of PbIMC1g is critical for proper IMC targeting, and PbIMC1g interacts with PbIMC1c. Conditional knockdown of PbIMC1g expression affects schizogony, gametogenesis, and ookinete conversion. PbIMC1g interacts with IMC1c to firmly anchor the glideosome to the subpellicular network. Additionally, we confirmed that IMC1g is functionally conserved in Plasmodium spp. These data reveal the function of IMC1g protein in anchoring the glideosome, providing further insight into the mechanism of the glideosome function.